Working for Equality : the Narrative of Harry Hudson. - Hudson, Harry (University of Georgia Press, 2015)
"When I went to work for Lockheed-Georgia Company in September of 1952 I had no idea that this would end up being my life's work." With these words, Harry Hudson, the first African American supervisor at Lockheed Aircraft's Georgia facility, begins his account of a thirty-six-year career that spanned the postwar civil rights movement and the Cold War. Hudson was not a civil rights activist, yet he knew he was helping to break down racial barriers that had long confined African Americans to lower-skilled, nonsupervisory jobs. His previously unpublished memoir is an inside account of both the ra